ON THE BIRTH OF JOURNAL OF NEONATAL SURGERY - Yogesh Kumar Sarin; Sushmita N Bhatnagar (EL-Med-Pub, 2012)
Neonatal surgery is the flagship and most challenging component of pediatric surgery; the quality of neonatal surgical service is a measure of the quality of pediatric surgical service provided by any centre.Through Journal of Neonatal Surgery, we intend to provide a portal to research and clinical material relating specifically to the surgical neonate. None of the existing six English journals of Pediatric Surgery devote even a small dedicated section to neonatal surgery. We believe that neonatal surgery has emerged a specialty in its own right over last two decades and should have a scientific journal devoted entirely to it.